Integrasi Pendidikan Karakter dalam Pembelajaran Pendidikan Agama Islam: Fondasi Etika Generasi Muda - M. Ainur Rafiq; Selfi Arinie; M. Khair; MR. Redha Anshari (Educompassion: Jurnal Integrasi Pendidikan Islam dan Global, 2025)
The Character education through Islamic Religious Education (PAI) has an important role in forming individuals with noble character. This study aims to explore the methods and impacts of character education in the context of PAI. The method used is a descriptive qualitative approach with a survey to collect data from various sources. The results of the study indicate that the internalization of moral and spiritual values in PAI not only teaches religious theory, but also encourages students to apply these values in everyday life. Exemplary behavior from parents and teachers, as well as the habituation of religious practices, are effective strategies in forming good character. In addition, the integration of character values in the PAI curriculum helps students understand and appreciate differences, and develop empathy and social responsibility. Thus, character education through PAI contributes significantly to the development of children's positive personalities, broad-mindedness, and ability to contribute to society. This study recommends the need to strengthen the PAI curriculum and training for educators to apply more effective educational methods in instilling character values.